Stochastic Effects for the Reaction-Duffing Equation with Wick-Type Product - Jin Hyuk Choi; SeungGwan Lee; Hyunsoo Kim (Advances in Mathematical Physics)
We construct new explicit solutions of the Wick-type stochastic reaction-Duffing equation arising from mathematical physics with the help of the white noise theory and the system technique. Based on these exact solutions, we also discuss the influences of stochastic effects for dynamical behaviors according to functions h1(t), h2(t), and Brownian motion B(t) which are the solitary wave group velocities.